A Multi-Modality Conversation Analysis of Post Expansions Among Physicians in Ambulance: A Qualitative Descriptive Study - Tian Y; Cui Y; Li X; Liu S; Su Y (Journal of Multidisciplinary Healthcare)
Yinong Tian,1 Yixuan Cui,2 Xin Li,1 Su Liu,3 Yonggang Su1 1School of Foreign Languages and Literature, Shandong University, Jinan, Shandong, People’s Republic of China; 2The First Clinical Medical College, Guangzhou University of Chinese Medicine, Guangzhou, People’s Republic of China; 3School of English, University of Sheffield, Sheffield, UKCorrespondence: Yonggang Su, School of Foreign Languages and Literature, Shandong University, Jinan, Shandong, People’s Republic of China, Email syg@sdu.edu.cnBackground: Ambulance communication is essential to emergency medical care, directly influencing patient outcomes, operational efficiency, and multidisciplinary collaboration. Effective communication is key to enabling physicians to treat the patients not the clock. There has been little research carried out in the ambulance setting to identify physicians’ communication challenges. The aim of this study was to qualitatively explore its sequence organization in the ambulance interaction through conversation analysis and to improve the clinical education associated with healthcare practice.Methods: Data collection took place within ambulances from an international hospital in China between May 2024 and October 2024. We undertook multi-modal conversation analysis on 10 videos, including 12 physicians, 10 patients and 8 companions, to examine the interaction among participants in the ambulance. Videos were transcripted based on the Jefferson Transcription System.Results: Different from other context, there is a significant variation in the way physicians response to the patients’ dispreferred responses in the ambulance. The recurring pattern, the request-dispreferred response-post expansion sequence, in ambulance communication is frequently seen. Physicians employ three hand gestures as effective post-expansions: holding hands, grabbing hands, and lifting hands, to enhance the multiparty coordination and improve the emergency efficiency.Conclusion: This study demonstrates how physicians secure tactical moments and interactional space with patients and companions in the ambulance within the institutional turn-taking mechanism. It furthers the understanding of ambulance physicians’ non-verbal behaviour by analyzing the interaction dilemma and provides a new perspective to help healthcare workers avoid the miscommunication and secure good communication in the medical emergency.Keywords: ambulance, conversation analysis, sequence organization